Overreactions in the Options Market - Stein, Jeremy (Journal of Finance, 1989)
This paper examines the “term structure” of options' implied volatilities, using data on S&P 100 index options. Because implied volatility is strongly mean reverting, the implied volatility on a longer maturity option should move by less than one percent in response to a one percent move in the implied volatility of a shorter maturity option. Empirically, this elasticity turns out to be larger than suggested by rational expectations theory—long-maturity options tend to “overreact” to changes in the implied volatility of short-maturity options.